A 2-step fast-track elastometry service for advanced workup of nonalcoholic fatty liver disease (NAFLD) patients – single-center real-world experience of outpatient clinical practice - Alsenbesy, Mohamed; Rau, Monika; Weiss, Johannes; Götze, Oliver; Geier, Andreas (Zeitschrift für Gastroenterologie, 2019)
Introduction and aims Nonalcoholic fatty liver disease (NAFLD) is increasing globally with an estimated prevalence of approximately 25 %. Nonalcoholic steatohepatitis as the progressive disease entity often leads to fibrosis and end-stage disease. The magnitude of NAFLD patients are not diagnosed and have no access to further clinical assessment. Diagnostic pathways for individual risk evaluation fitting with available resources are of utmost importance in real-world clinical practice.Methods Retrospective analysis of 1346 anonymized outpatient datasets at Würzburg University Hospital, Germany. Transient elastography (TE) with controlled attenuation parameter and laboratory-based risk scores (NFS, FIB-4) were the main diagnostic workup tools for risk stratification.Results After preselection based on questionnaire information NAFLD still accounts for one-fifth of patients in the liver outpatient service. More than 80 % of NAFLD patients receive their first-time diagnosis in our unit. Laboratory-based risk scores and TE are valuable tools for second-step risk assessment as shown in our clinical data analysis. Moreover, 65 % of NAFLD patients use inpatient services for at least 1 day. The policy to perform liver biopsy in high-risk patients above the recommended threshold of 9.6 kPa if any clinical doubt exists regarding the diagnosis of cirrhosis leads to a histological down staging in almost 80 %.Conclusion Questionnaire-based referral from primary care followed by broadly available fast-track TE and eventually liver biopsy for selected patients is the standard practice in our unit. This approach represents a feasible model to handle the large gap between availability and clinical need for TE facilities.
Keywords: nonalcoholic fatty liver disease (NAFLD); nonalcoholic steatohepatitis (NASH); transient elastography (TE); controlled attenuation parameter (CAP); diagnostic algorithm; risk assessment; NAFLD fibrosis score (NFS) and fibrosis-4 index (FIB-4); outpatient clinic; referral form